Parameter Ambang Dalam Regresi Wavelet - Suanto, Elfis (Jurnal Pilar Sains, 2003)
Considered a regression model yi=f (ti)+ei ,i= 1,2 ,3 ,....,n where ei assumed iid N(0, ). To found the best estimator of fungtion f in regression waveletswill be associated with chosen threshold parameter t. The Cross-Validation method is a goodto choose the parameter t.